Emek - Onyefulu, Ifeoma (Cobblehill Books, 1995)
This is a concept book to teach and delight. As a young African boy travels to visit his grandmother, he passes through the village market, where he sees lots of things Granny would like? four brooms, five hats, six necklaces, seven musical instruments, and so on. Stunning photographs taken in Emeka's southern Nigerian village illustrate this heartwarming story. "A wonderful multidimensional story with universal appeal."